2016
DOI: 10.3171/2016.2.spine151295
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D CT-based navigation in minimally invasive lateral lumbar interbody fusion

Abstract: OBJECTIVE Lateral lumbar interbody fusion (LLIF) is an increasingly popular technique used to treat degenerative lumbar disease. The technique of using an intraoperative cone-beam CT (iCBCT) and an image-guided navigation system (IGNS) for LLIF cage placement has been previously described. However, other than a small feasibility study, there has been no clinical study evaluating its accuracy or safety. Therefore, the purpose of this study was to evaluate the accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 15 publications
4
26
0
Order By: Relevance
“…Park 2015 found that this method of navigation was safe, feasible and appeared to be accurate in LLIF procedures (8). This finding is similar to that of Joseph et al, who also used intraoperative CT and an image-guided navigation system for LLIF cage placement (16). A literature review of 26 prospective clinical trials also found that the percentage of inserted screws contained within the pedicle was 89% to 100% when using CT navigation (15).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Park 2015 found that this method of navigation was safe, feasible and appeared to be accurate in LLIF procedures (8). This finding is similar to that of Joseph et al, who also used intraoperative CT and an image-guided navigation system for LLIF cage placement (16). A literature review of 26 prospective clinical trials also found that the percentage of inserted screws contained within the pedicle was 89% to 100% when using CT navigation (15).…”
Section: Discussionsupporting
confidence: 66%
“…Similar results have been found in several reports using CT-based spinal navigation with lateral lumbar interbody fusion (LLIF) (8,16). The use of CT navigation with anterior lumber interbody fusion (ALIF) has also been shown to provide greater accuracy and less variation in device placement, though only in cadaveric models (14).…”
Section: Introductionsupporting
confidence: 71%
“…Accuracy results for 50 patients (95%) who had all pedicle screws installed with computer assistance proved statistically better than results for a control group of 100 patients (85%) instrumented with a conventional technique using biplanar fluoroscopy [16]. Similar screw placement accuracies are reported in multiple recent studies with navigation-assistance, all using postoperative CT scan to determine the screw placement accuracy [11,12,[17][18][19][20]. Most studies reported 98% to 99% of their screws being placed within a 2 mm pedicle breach margin despite slightly different methods of screw placement.…”
Section: Discussionsupporting
confidence: 55%
“…Computerized tomography-based spinal image guidance has evolved from paired point matching, paired point matching combined with surface matching [9], three dimensional rotational X-ray [10], three dimensional CT based navigation [11]. The accuracy of the navigation system depending on the integrity of the connected components of the system, and the stability of DRF, which are the critical parts of navigation surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation